Ledderhose Disease: Clinical, Radiological (Ultrasound and MRI), and Anatomopathological Findings - Omor, Y. (Case Rep Orthop, 2015)
Plantar fibromatosis, or Ledderhose disease, is a rare hyperproliferative disorder of the plantar aponeurosis. It may occur at any age, with the greatest prevalence at middle age and beyond. This disorder is more common in men than woman and it is sometimes associated with other forms of fibromatosis. Diagnosis is based on clinical examination. Ultrasound (US) and magnetic resonance imaging (MRI) can be useful to confirm the diagnosis. A 44-year-old man with Ledderhose disease who underwent ultrasound and MR is described in this paper.